Neuronal Avalanches Across the Rat Somatosensory Barrel Cortex and the Effect of Single Whisker Stimulation - Mariani, Benedetta; Nicoletti, Giorgio; Bisio, Marta; Maschietto, Marta; Oboe, Roberto; Leparulo, Alessandro; Suweis, Samir; Vassanelli, Stefano (Frontiers in Systems Neuroscience, 2021)
Since its first experimental signatures, the so called `critical brain hypothesis' has been extensively studied. Yet, its actual foundations remain elusive. According to a widely accepted teleological reasoning, the brain would be poised to a critical state to optimize the mapping of the noisy and ever changing real-world inputs, thus suggesting that primary sensory cortical areas should be critical. We investigated whether a single barrel column of the somatosensory cortex of the anesthetized rat displays a critical behavior. Neuronal avalanches were recorded across all cortical layers in terms of both \textcolor{red}{multi-unit activities} and population local field potentials, and their behavior during spontaneous activity compared to the one evoked by a controlled single whisker deflection. By applying a maximum likelihood statistical method based on timeseries undersampling to fit the avalanches distributions, we show that neuronal avalanches are power law distributed for both \textcolor{red}{multi-unit activities} and local field potentials during spontaneous activity, with exponents that are spread along a scaling line. Instead, after the tactile stimulus, activity switches to \textcolor{red}{a transient} across-layers synchronization mode that appears to dominate the cortical representation of the single sensory input.